SPECIES COMPOSITION, STRUCTURE AND CARBON STOCKS OF DEADWOOD OF THE «KOLOGRIVSKY LES» NATURE RESERVE FORESTS AFTER THE CATASTROPHIC WINDTHROW OF 2021 - A. V. Lebedev; N. V. Ivanova; D. Yu. Gosteva; V. V. Gostev; I. G. Krinitsyn; M. P. Shashkov (Вопросы лесной науки)
Catastrophic windthrows lead to dramatic damages in the structure of forest stands, the consequences of which are complex and long-term in scope. The aim of the study was to assess changes in carbon stocks of deadwood and the structure of even-aged and uneven-aged old-growth forest stands in the Kologrivsky Forest Nature Reserve after the storm of 2021 using ground-based data. A total of 15 sample plots were established on areas of different wind damages in the Kologrivsky cluster of the Reserve in July 2022 to evaluate the storm impact on forest stands. A visual forest inventory was carried out to estimate the growing part of the stand that survived the catastrophic impact. The fallen fraction of the stand was studied on transects in the same sample plots. The trunk diameter of each deadwood trunk was measured, the species was identified, and the decomposition stage was assessed during this survey. Three different ways for the deadwood carbon stock evaluation on transects were used. These methods were based on the basic wood density at different stages of decomposition and how the carbon content in deadwood changes with its volume. The greatest diversity of decomposition stages and tree species diversity in the deadwood were found in mixed linden-spruce stands. Trunks of the first decomposition stage were dominated in structure of deadwood in the even-aged fir-spruce, spruce, birch, and aspen stands, while the fraction of other stages was relatively low. Birch and aspen showed the highest resistance to storm winds, while spruce was less resistant. The proportion of windfall spruce deadwood was 79%, and birch and aspen were 34% of the stock on average before the windthrow. The largest carbon stock in deadwood was found in pure and near-pure even-aged mature and overmature spruce stands in the Sekha and Ponga river basins, reaching 65.3–68.8 tonnes C per ha in some areas.